Mandatory e-government has arrived: The silent protest from staff calls for the committed scholar – resistance must never be futile! - Berger, Jesper Bull (ACIS, 2014)
The great potential in e-government - the provision of public services to citizens through the internet - is widely recognized by governments and expectations of the benefits are high. E-government research has been preoccupied with its evolution, public websites and citizen adoption from a ‘natural growth and voluntary use’ perspective. Little attention has been drawn to mandatory e-government. This paper reports from an exploratory study on a Danish mandatory e-government initiative – enforced e-communication between local government and citizens. Civil servants’ perception was investigated through two Focus groups. Civil servants reported that some citizens find it really hard to manage computer and e-communication. Moreover, the civil servants feel that they are not allowed to offer the necessary assistance, which makes them frustrated. They find that especially weak citizens may lose welfare benefits due to e-communication. This has a negative effect on motivation and work life quality and may affect the public sector ethos. Increased efficiency by mandatory e-government may be the next hype. How will it affect citizens, civil servants and the ‘public good’? How can it ensure that citizens’ rights are not violated? This paper calls for critical research on e-government impact and for e-government scholars to play an active part ensuring ethical e-government.